On-line coupling of pressurized capillary electrochromatography with end-column amperometric detection for analysis of estrogens - Liu, Shaofeng; Wu, Xiaoping; Xie, Zenghong; Lin, Xucong; Guo, Liangqia; Yan, Chao; Chen, Guonan (Electrophoresis, 2005)
An improved technique, pressurized capillary electrochromatography (pCEC) coupling with end‐column amperometric detection (AD), was developed and used for the separation and determination of estrogens. The effects of pH value, composition of mobile phase, concentration of the surfactant sodium dodecyl sulfate (SDS) and applied voltage on separation were investigated. The electrochemical oxidation of diethylstilbestrol (DES), dienestrol (DE), and hexestrol (HEX) could be reliably monitored with a carbon electrode at 0.9 V (vs. Ag/AgCl). The pCEC analyses were performed on a capillary separation column packed with 3 µm C18 particles with an acetonitrile/water (31%: 69%) mobile phase containing Tris buffer (5 mmol/L, pH 4.5) and 4 mmol/L SDS. High voltage up to 12 kV reduced the retention time dramatically and still provided a baseline resolution. In addition, supplementary pressure prevented bubble formation and provided reliability and reproducibility of the pCEC performance. The detection limits for the three estrogens ranged from 1.2 to 2.2×10−7 mol/L, about 10˜20‐fold lower than those obtained with pCEC‐UV detection. To evaluate the feasibility and reliability of this system, the proposed pCEC‐AD method was further demonstrated with fish muscle samples spiked with estrogens.